2020
DOI: 10.1016/j.waojou.2020.100127
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal age at delivery and allergic rhinitis in schoolchildren: A population-based study

Abstract: Background: Some studies have shown associations of maternal age at delivery with asthma and food allergy in offspring. However, the relationship between maternal age at delivery and allergic rhinitis is largely unclear. This study aimed to investigate the association between maternal age at delivery and allergic rhinitis in a population sample of Asian children, and to explore potential effect modifiers.Methods: A total of 1344 singleton-birth children (763 boys, 56.8%; mean age, 6.4 years) participating in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Paternal age at birth was analyzed either as a continuous variable or as a categorical variable with four groups, including < 30 (reference group), 30–34, 35–39, and ≥ 40 years. The adjusted covariates were listed as follows: child’s age, sex, height, maternal age at birth, prematurity (gestational age less than 37 weeks), birth weight, cesarean delivery, birth order, physician-diagnosed asthma, parental university education, parental allergic diseases (physician-diagnosed asthma, allergic rhinitis or atopic dermatitis in mother, father or both), prenatal exposure to ETS (one or more household smokers during gestation), breastfeeding (exclusive or partial) longer than 6 months, and household income, which were similar to previous relevant studies [ 12 , 14 , 17 , 23 ]. We performed subgroup analysis, stratified by prenatal exposure to ETS and breastfeeding which were associated with lung function and FeNO in previous studies [ 24 – 29 ], to evaluate potential effect modifiers.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Paternal age at birth was analyzed either as a continuous variable or as a categorical variable with four groups, including < 30 (reference group), 30–34, 35–39, and ≥ 40 years. The adjusted covariates were listed as follows: child’s age, sex, height, maternal age at birth, prematurity (gestational age less than 37 weeks), birth weight, cesarean delivery, birth order, physician-diagnosed asthma, parental university education, parental allergic diseases (physician-diagnosed asthma, allergic rhinitis or atopic dermatitis in mother, father or both), prenatal exposure to ETS (one or more household smokers during gestation), breastfeeding (exclusive or partial) longer than 6 months, and household income, which were similar to previous relevant studies [ 12 , 14 , 17 , 23 ]. We performed subgroup analysis, stratified by prenatal exposure to ETS and breastfeeding which were associated with lung function and FeNO in previous studies [ 24 – 29 ], to evaluate potential effect modifiers.…”
Section: Methodssupporting
confidence: 87%
“…This study is a part of the Longitudinal Investigation of Global Health in Taiwanese Schoolchildren (LIGHTS) study, which is a population-based longitudinal cohort included 1513 children born during 2010-2011 in the Chang Gung Memorial Hospital [16][17][18][19]. The majority of these children lived in northwestern Taiwan.…”
Section: Subjectsmentioning
confidence: 99%
“…This study recruited 165 Asian children (92 stable asthmatic children and 73 non‐asthmatic controls) among participants aged 5‐7 years participating in the Longitudinal Investigation of Global Health in Taiwanese Schoolchildren (LIGHTS) cohort 17 . Among those, 165 study subjects were divided into two independent sets: a training set of 60 asthmatic children and 41 non‐asthmatic controls enrolled in 2016, and a validation set of 32 asthmatic children and 32 non‐asthmatic controls enrolled in 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The LIGHTS population-based cohort consists of 1513 children who were born in 2010 and 2011 and attended well-child visits and follow-up visits in the Chang Gung Memorial Hospital (CGMH). 20 , 21 , 22 After excluding multiple births ( n = 162) and missing data on asthma or atopy ( n = 8), 1343 children were included in the present study. The flow chart for the enrollment process of study subjects is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%